Penerapan Strategi Pembelajaran Billboard Ranking Guna Meningkatkan Prestasi Belajar Sejarah Materi Perkembangan Masyarakat Indonesia Pada Masa Reformasi Pada Siswa Kelas VII A SMP Negeri 1 Cenrana - sudirman sudirman (Universitas Negeri Makassar, 2019)
Abstract. The problems that want to be studied in this study are: (a) How is the increase in student learning achievement by the application of Billboard Ranking learning. (b) What is the influence of the Billboard Ranking learning method on student learning achievement. The purpose of this action research is: (a) Want to know the improvement of student learning achievement after the implementation of Billboard Ranking learning. (b) Want to know the effect of student learning motivation after the implementation of the Billboard Ranking learning method. This study uses action research as many as three rounds. Each round consists of four stages, namely: design, activity and observation, reflection, and refining. The target of this study is students of Class VII A. Academic Year 2016/2017. Data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement had increased from cycle I to cycle III, namely, cycle I (59%), cycle II (79%), cycle III (88%). The conclusion of this study is the Billboard Ranking method can have a positive effect on the learning motivation of Class VII A. Students in 2016/2017 lessons, and this learning method can be used as an alternative to learning history.